Local rates of new firm formation: An empirical exploration using Swedish data - Martin Andersson; Niclas Lavesson; Mark D. Partridge (Research Institute of Industrial Economics (IFN), 2019)
We assess the empirical literature on the determinants of spatial variations in new-firm formation rates by undertaking a systematic empirical analysis of the relative roles of different demand- and supply-side factors. Using instrumental variables to address endogeneity, we find that local growth drives local entrepreneurship exclusively in services industries. Average establishment size has a robust negative influence on local new-firm formation rates, but its effect varies across industries. Local industry diversity is only positive for new-firm formation in high-tech and knowledge-intensive activities. There is also some evidence of that longer distances to urban centers is associated with higher new-firm formation rates. The only local factor with a consistent positive effect on new-firm formation across industries is local density of skilled workers. We conclude that industry structure, geography and agglomeration matter, but in the end, new firms are started by people, so it is unsurprising that the main factor driving local entrepreneurship is the characteristics of the local residents.
Keywords: R11; L26; M13; R30; 330; Entrepreneurship; New firm formation; Geography; Human capital; Agglomeration; Local growth; Startups